2016
DOI: 10.1002/cbdv.201500516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 3,5‐Dimethoxystilbene Analogs

Abstract: In our continuing effort to discover natural product-based pest management agents, derivatives of 3,5-dimethoxystilbene were synthesized yielding 27 new and six known compounds. Compounds 11 and 12 showed strong Aedes aegypti larvicidal activity (LC 45.31 and 49.93 μm, respectively). Furthermore, 11 and 12 exhibited high effectiveness against larvae of pesticide-susceptible and pyrethroid-resistant strains of Ae. aegypti; activity against the adult mosquitoes was low. Compounds 6f, 6g, and 6i at either 83.3 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…All the target compounds were identified and characterized by 1 H-NMR, 13 C-NMR and ESI-HRMS. In the 1 H-NMR spectra of the target compounds, the signals of the vinylic CH proton connected to the thiazole ring were observed at around 6.93–7.38 ppm, and the peaks of the vinylic CH proton connected to the benzene ring appeared in the 7.10–7.64 ppm range, generally appearing as a doublet with a coupling constant J = 16.0 Hz or 16.5 Hz, which indicated that the target compounds are of the E -configuration [ 30 ]. In the 13 C NMR spectra, the signals of the vinylic carbon adjacent to the thiazole ring could be found at around 119.3–124.6 ppm, and the peaks of the vinylic carbon adjacent to the benzene ring were observed in the range of 130.8–137.9 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…All the target compounds were identified and characterized by 1 H-NMR, 13 C-NMR and ESI-HRMS. In the 1 H-NMR spectra of the target compounds, the signals of the vinylic CH proton connected to the thiazole ring were observed at around 6.93–7.38 ppm, and the peaks of the vinylic CH proton connected to the benzene ring appeared in the 7.10–7.64 ppm range, generally appearing as a doublet with a coupling constant J = 16.0 Hz or 16.5 Hz, which indicated that the target compounds are of the E -configuration [ 30 ]. In the 13 C NMR spectra, the signals of the vinylic carbon adjacent to the thiazole ring could be found at around 119.3–124.6 ppm, and the peaks of the vinylic carbon adjacent to the benzene ring were observed in the range of 130.8–137.9 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Tamoxifen (a phenylstilbene compound) is being explored as an anti-mycobacterial drug, acting as a host-directed therapeutic that assists macrophages in killing mycobacterial cells [ 19 , 20 , 21 ]. Analogs of 3,5-dimethoxystilbene had MIC values that ranged from 61.68 and 74.04 μg/mL against M. intracellulare [ 22 ]. The 3-fluoro-Z-stilbene exhibited an MIC of 26 μg/mL against M. bovis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%